2015
DOI: 10.1159/000440940
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Left and Right Myocardial Function in Preterm Infants Using Strain and Strain Rate Imaging

Abstract: Background: There is a paucity of longitudinal data on left ventricular (LV) and right ventricular (RV) function in preterm infants of less than 29 weeks' gestation. Objective: The aim of this study was to describe changes in tissue Doppler-derived basal longitudinal strain (BLS) and systolic (SRs), early (SRe) and late (SRa) diastolic strain rates in extremely premature infants from birth to 36 weeks postmenstrual age (PMA). Methods: Echocardiographic assessments were carried out on days 1, 2, 5-7 and at 36 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 27 publications
(35 reference statements)
4
56
2
Order By: Relevance
“…16 Interestingly, deformation indices were also higher in the RV than the LV beginning at 32 weeks PMA and persisting to one year CA, which is in concordance with previous studies in children and neonates. 22,35,36 In this study, the increase of RV and IVS strain in uncomplicated preterm infants was influenced by both postnatal increase in weight (in grams) and post-gestational age (in weeks), Figure 3. The relative higher values of RV strain and its progressive increase throughout the late neonatal period and infancy (when compared to LV strain) is probably related to the more longitudinal orientation of RV fibers with a predominant longitudinal contraction pattern in the RV compared to the LV.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…16 Interestingly, deformation indices were also higher in the RV than the LV beginning at 32 weeks PMA and persisting to one year CA, which is in concordance with previous studies in children and neonates. 22,35,36 In this study, the increase of RV and IVS strain in uncomplicated preterm infants was influenced by both postnatal increase in weight (in grams) and post-gestational age (in weeks), Figure 3. The relative higher values of RV strain and its progressive increase throughout the late neonatal period and infancy (when compared to LV strain) is probably related to the more longitudinal orientation of RV fibers with a predominant longitudinal contraction pattern in the RV compared to the LV.…”
Section: Discussionmentioning
confidence: 60%
“…19 In a small comparative study of preterm and term infants from birth to six months of age, Schubert et al observed an increasing upward trend in RV and IVS strain values. 16 In larger studies, both Hefler and Cerznick 38 and James et al 11,22 observed that tissue Doppler- derived RV and IVS strain values rose significantly from birth to 28 days of age and 36 weeks PMA, respectively. With 2DSTE-derived strain, Czernik et al also observed a rise in IVS GLS over the first 28 days of age.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…RV s′ was measured using pulse wave at the base of the RV free wall 18. Finally, RV peak systolic BLS (RV BLS) was obtained from the apical four-chamber view using tissue Doppler-derived deformation imaging as previously described 15 19 20. Our group and others have previously demonstrated the feasibility and reproducibility of all the RV measures described in this study 1 12 15…”
Section: Methodsmentioning
confidence: 96%
“…Strain is calculated as a spatial derivative of SR, is measured along the beam of the ultrasound, and is insonation angle dependent. cDTI is better suited for measurement of SR values in neonates (with a higher baseline heart rate) as it employs a natural SR calculation method with much higher frame rates (high temporal resolution) [49,50] . This technique is highly feasible and reproducible, but the disadvantages of this approach are the dependence on the angle of insonation (>20° results in a significant underestimation of values) and loading conditions [51] .…”
Section: Deformation Imagingmentioning
confidence: 99%